Primary Prevention: No Associations of Strength and Cardiorespiratory Fitness Status With Arterial Stiffness in Young School Children - Kirchhuebel, Hannah; Oberhoffer, Renate; Böhm, Birgit (Frontiers in Pediatrics, 2020)
Pulse wave velocity (PWV) and central systolic blood pressure (CSBP) are well-established biomarkers of arterial stiffness. Fitness is known to be an important protective factor in adults in respect of vascular stiffening. The association of both muscular and cardiorespiratory fitness (CRF) with arterial properties in children has been inconsistent. The aim of the study was to investigate the relationship between anthropometric data, CRF, strength and arterial stiffness parameters in German children. 76 children, age 6 to 11 years (63.2% males) were examined. Peripheral systolic blood pressure (PSBP) [mmHg], peripheral diastolic blood pressure (PDBP) [mmHg] and PWV [m/s] were measured noninvasively after 10 minutes of rest with the oscillometric cuff-based Mobil-O-Graph (IEM, Healthcare, Stolberg). CSBP [mmHg] was calculated using the ARCSolver Algorithm (Austrian Institute of Technology, Vienna) based on the recorded brachial pulse waves. CRF was measured using the validated Progressive Aerobic Cardiovascular Endurance run (PACER), also called shuttle-run test, for estimating maximal aerobic capacity (VO2max). Hand-grip strength [kg] as an indicator of overall muscle strength was determined with the Jamar Analogue Hand Dynamometer. For more detailed analyses, the study group was divided into subcohorts; a risk group, including children with abnormal blood pressure or high body weight, and a healthy subgroup. Healthy children showed a positive association between PWV and body mass index (BMI) (p= 0.016) and CSBP and BMI (p= 0.033), respectively. Hand-grip strength was positively associated with CSBP (left: p= 0.013, right: p= 0.015) and PWV (left: p= 0.008, right: p= 0.002), as well as the number of shuttle run rounds were positively correlated to PWV (p= 0.038) in the whole cohort. No significant association of converted VO2max with PWV were found. The multivariate regression analysis explained 38.8% (R2=0.388) of the variance and the model was a significant predictor of PWV (F (6,29) = 3.060, p= 0.019), however, none of the integrated covariates (age, sex, BMI, number of shuttle run rounds, VO2max, dominant hand-grip strength) contributed significantly to the model. The lack of associations between fitness, strength and arterial stiffness might be explained by the few harmful lifestyle factors influencing vascular changes in the first decade of life.